Traditional vs. ESG Signals in Value Creation: A Study of Market Value Added - Șandru, Raluca (The Journal of Accounting and Management, 2025)
This paper examines the determinants of MVA for firms listed on the Bucharest Stock Exchange. It focuses on the signaling role of net profit, solvency, and liquidity, as well as the growing importance of ESG practices from 2020 to 2025. The objective is to understand how firms can credibly signal value in a volatile, sustainability-driven context. Previous research (2006–2013) revealed a positive correlation between profit and MVA, a negative correlation between solvency and MVA, and an insignificant correlation between liquidity and MVA. However, this framework predates recent structural economic shocks and the growing importance of ESG. Building on signaling theory, this study questions whether traditional financial indicators still dominate or if new nonfinancial signals are reshaping market expectations. Due to incomplete datasets, the research employs a comparative, scenario-based methodology rather than quantitative regression. Scenarios are constructed to test the interactions between financial and ESG indicators. Profit remains the strongest driver of MVA; solvency continues to transmit negative signals; liquidity shows marginal influence; and ESG emerges as a critical differentiator that can amplify or offset financial signals. These findings challenge firms and policymakers to move beyond the traditional financial paradigm and integrate ESG into their value creation strategies.